Biodegradation of natural phenolic compounds as single and mixed substrates by Fusarium flocciferum - Mendonça, Elsa; Martins, Aida; Anselmo, Ana Maria (Electronic Journal of Biotechnology, 2004)
The mycelium of Fusarium flocciferum was assayed for its ability to degrade aromatic compounds, namely, gallic, protocatechuic, vanillic, syringic, caffeic, and ferulic acids and syringic aldehyde, commonly found in agro-industrial wastes. The biodegradation assays were performed in liquid medium with the phenolic compounds as single substrates and as a synthetic mixture containing the seven aromatic compounds. The results with single substrates indicated that in 24 hrs of incubation the fungus was able to reduce the phenolic concentration from 200 mg/l to below detection limits, except for syringic acid, being the lowest degradation rates found for this acid and its aldehyde. The biodegradation experiments with the mixture of phenolic compounds showed that after 8 hrs the total phenolic concentration was reduce from 350 mg/l to below the detection limits of all the tested compounds. In all the experiments a rise in the pH and an effective detoxification of the phenolic solutions were also observed.